2011
DOI: 10.1136/bjsm.2010.081992
|View full text |Cite
|
Sign up to set email alerts
|

Shockwave treatment for medial tibial stress syndrome in athletes; a prospective controlled study

Abstract: Objective The purpose of this study was to describe the results of two treatment regimens for medial tibial stress syndrome (MTSS); a graded running programme and the same running programme with additional shockwave therapy (extracorporeal shockwave therapy; ESWT). Design A prospective observational controlled trial. Setting Two different sports medicine departments. Participants 42 athletes with MTSS were included. Intervention Patients from one hospital were treated with a graded running programme, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 29 publications
0
65
0
1
Order By: Relevance
“…Moen et al 18 reported that five sessions of focused ESWT added to a graded running programme reduced significantly the time to full recovery (mean 32 days) compared with the running programme in isolation, as assessed by a treadmill running test. On the contrary, a high-quality, low risk of bias RCT20 that used the same ESWT protocol without additive controlled intervention reported no significant differences at 10-week follow-up between ESWT and sham dose ESWT groups in pain during muscle pressure (patient-rated improvement of ‘no change’ and ‘minimally improved’, respectively), pain-limited distance run and self-perception of change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moen et al 18 reported that five sessions of focused ESWT added to a graded running programme reduced significantly the time to full recovery (mean 32 days) compared with the running programme in isolation, as assessed by a treadmill running test. On the contrary, a high-quality, low risk of bias RCT20 that used the same ESWT protocol without additive controlled intervention reported no significant differences at 10-week follow-up between ESWT and sham dose ESWT groups in pain during muscle pressure (patient-rated improvement of ‘no change’ and ‘minimally improved’, respectively), pain-limited distance run and self-perception of change.…”
Section: Resultsmentioning
confidence: 99%
“…One study19 used the same low-energy protocol of radial ESWT for three sessions (energy flux density 0.1mJ/mm 2 ), while the other18 used a graded energy protocol of focused ESWT for five sessions (energy flux density from 0.1 to 0.3 mJ/mm 2 ), resulting in more than the double total energy flux. Contradictory results at short-term follow-up were presented by the only RCT20 that used the same ESWT protocol as a non-randomised study 18. Several considerations are raised regarding the effectiveness of ESWT as well as the dose of the mechanical energy to be transferred.…”
Section: Discussionmentioning
confidence: 99%
“…37 Nominal levels of 14-31 MPa were used to explore shock wave treatment for tibial stress syndrome in athletes. 38 Characterization of the acoustic fields produced by medical devices is usually performed in water and then the results are translated (derated) into tissue, where direct measurements are impossible in most cases. In recent studies, numerical modeling combined with measurements has been actively used to characterize acoustics fields from highpower ultrasound medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…rESWT has been used to treat numerous other tendinopathies, such as epicondylitis,22,26 plantar fasciitis,26–28 patellar tendinopathy,21,26,29 shoulder calcific tendinitis,19,30,31 proximal hamstring tendinopathy,32 and medial tibial stress syndrome 20,33. However, to the authors’ knowledge, to date, no studies on rESWT and trigger digit have been conducted.…”
Section: Introductionmentioning
confidence: 99%